Presentation: Community Justice in the Andes (II) - Peña Jumpa, Antonio (2002)
The Andean community organizations (peasant communities, peasant rounds, ayllus, markas, partialities, annexes, hamlets, cantons or rural towns) and the community organizations of the Amazon (native communities, hamlets, annexes, sectors or rural towns) show a particular self-resolution of conflicts. Historically, and according to their needs, as well as their own alternatives for resolving their conflicts.